Thinning intensity inhibits microbial metabolic limitation and promotes microbial carbon use efficiency in natural secondary forests in the Qinling Mountains - Song, Yahui; Yang, Hang; Huang, Dongcai; Yan, Chenglong; Kang, Haibin; Qi, Haiyu; Yu, Hang; Wang, Dexiang (Forest ecology and management, 2024)
Forest ecosystems are important carbon (C) pools in terrestrial ecosystems, and the decomposition of soil organic matter depends on soil microbial metabolism. This study aimed to determine how forest thinning affects microbial metabolic limitation and microbial carbon use efficiency (CUE). We determined microbial metabolic limitations via extracellular enzymatic stoichiometry and microbial CUE by using a biogeochemical equilibrium model under different thinning intensities in the Qinling Mountains. We also analyzed the relationships among microbial metabolic processes and soil enzymes, soil properties (i.e., pH, soil nutrition content, and stoichiometry), and soil microbial biomass (i.e., microbial biomass and stoichiometry). Soil microbial metabolism was limited by C and phosphorus under the thinning intensities, and mild and moderate thinning intensities reduced the soil microbial C limitation. The effect of thinning intensity on CUE in the subsoil was greater than that in the topsoil. The pathways of CUE in the topsoil and subsoil differed, and microbial biomass and soil nutrients were the main factors affecting CUE in the topsoil and subsoil, respectively. Thinning changes the CUE by directly affecting microbial biomass in the topsoil, and thinning affects soil microbial biomass indirectly by affecting soil nutrients (i.e., total phosphorus), changing CUE in the subsoil. Our results show that moderate thinning can alleviate microbial metabolic limitation, and this finding has implications for understanding how microbial metabolism affects soil C dynamics under forest thinning. •Forest thinning altered microbial metabolic limitation.•Soil microbes were limited by the C and P under different thinning intensities.•Moderate thinning alleviated microbial metabolic limitation.•Forest thinning changed carbon use efficiency by affecting microbial biomass.